Fetomaternal Outcome in Teenage Pregnancy at Tertiary Care Hospital Quetta - Aman, Asiya; Hira; Baloch, Samina; Ali, Saira; Naeem, Samina; Abdullah Jan, Zainab; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2024)
Introduction: Pregnancy in teenage is a major public health problem throughout the world and is globally recognized as high-risk pregnancy, leading to a vicious circle of various physical, social, and medical concerns from which it is very difficult for a girl and her fetus to get scape. It is important to study the implication of the maternal and fetal health in teenage pregnancy. Objective: To determine fetomaternal outcomes in teenage pregnancy at tertiary care hospital Quetta. Material and Methods: This was a cross-sectional study (descriptive study) conducted at Department of Obstetrics & Gynecology, Bolan Medical Complex Hospital Quetta over a period of six months from 1st May 2023 to 31th October 2023. Results: There were 136 patients enrolled in the study. The mean gestational age of babies delivered by teenage pregnant women was found to be 32.52 ± 2.966 weeks. In our study, fetomaternal outcomes were assessed that were analyzed on individual basis initially. In our study relationship between patient’s place of residence was assessed with fetomaternal outcomes. There was significant relationship was found between patient’s place of residence with maternal anemia, primary postpartum hemorrhage, pre-eclampsia, pregnancy induced hypertension, low birth weight babies, fetal distress and poor APGAR scores respectively. Conclusion: Teenage pregnancy significantly impacts on fetomaternal outcomes in our study in the form of maternal anemia, primary postpartum hemorrhage, pre-eclampsia, pregnancy induced hypertension, low birth weight babies, fetal distress and poor APGAR scores. Education of female child, their families regarding delaying marriages, hence delaying childbearing can interrupt vicious circle of complications of teenage pregnancy.